Dirty Bertie Mud - MacDonald, Alan.; Roberts, David (London : Stripes Publishing, 2009)
Join Bertie as he faces a barrage of footballs as the school's new goalie, battles to stay clean for the school photographer and gets hopelessly lost in a huge department store.
3-6.
Turkish.
Keywords: Behavior -- Fiction; Football -- Fiction